Semianalytical Modelling and 2D Numerical Simulation of Low-Frequency Noise in Advanced N-Channel FDSOI MOSFETs. (3rd December 2020) - Boutchacha, T.; Ghibaudo, G.
Abstract : Thorough investigations of the low-frequency noise (LFN) in a fully depleted silicon-on-insulator technology node have been accomplished, pointing out on the contribution of the buried oxide (BOX) and the Si-BOX interface to the total drain current noise level. A new analytical multilayer gate stack flat-band voltage fluctuation-based model has been established, and 2D numerical simulations have been carried out to identify the main noise sources and related parameters on which the LFN depends. The increase of the noise at strong inversion could be explained by the access resistance contribution to the 1/f noise. Therefore, considering uncorrelated noise sources in the channel and in the source/drain regions, the total low-frequency noise can simply be obtained by adding to the channel noise the contribution of the excess noise originating from the access region (Δ r ). Moreover, only two fit parameters are used in this work: the trap volumetric density in the BOX, and the 1/f access noise level originating from the access series resistance, which is assumed to be the same for the front and the back interfaces.